Reading and Writing Ability of Dyslexic Students Through Simultaneous Multisensory Teaching (SMT) Method - Nirmala, Sri Dewi; Ong, Eng Tek; Thoe, Ng Khar; Anggoro, Subuh (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2023)
ABSTRACT The purpose of this study is to analyze the use of the Simultaneous Multisensory Teaching method (SMT) on improving reading and writing skills of dyslexic students . Students with dyslexia in addition to having difficulty in writing, also generally have difficulty in reading and mentioning a letter, word, and sentence, and often reverse in writing and mentioning letters. One of the methods recommended by International Dyslexia Association (IDA) in improving reading and writing skills of dyslexic students is the Simultaneous Multisensory Teaching (SMT) method. SMT is a special method for students with dyslexia. The learning process goes through special stages to develop students' abilities by optimizing several senses in an integrated manner. The subjects in this study were single participants, namely students with dyslexia with the initials AMJ , who were Grade IV students at SDN 1 Pasirlangkap, Cikidang District, Sukabumi Regency . This research uses an approach qualitative with descriptive method . Data collection techniques using interviews, observation, and documentation. Data analysis techniques consist of: 1) data reduction, 2) data presentation, and 3) drawing conclusions. The results showed that gradually the students' reading and writing abilities began to improve by using the SMT method . The ability to recognize letters that are often confused has begun to be mastered, both in pronunciation while reading and writing. Similarly, reading and writing words and sentences, there has been a change compared to the initial observations, which tend to have a lot of writing errors. Based on this, it can be concluded that the use of the SMT method can improve the reading and writing skills of dyslexic students.